Synthesis, characterization and in vitro investigation of nanocellulose reinforced chitosan hydrogel for enhancing bioavailability of curcumin / Thennakoon Mudiyanselage Sampath Udeni Gunathilake - Thennakoon Mudiyanselage, Sampath Udeni Gunathilake (2019)

(untitled)
A unique biodegradable, superporous, swellable and pH sensitive nanocellulose reinforced chitosan hydrogel with dynamic mechanical properties was prepared for enhancing bioavailability of curcumin. Rod-shaped cellulose nanocrystals (CNCs) that were approximately 200–300 nm in length and 40–50 nm in width were prepared from microcrystalline cellulose via sulfuric acid hydrolysis. CNC ratios of 0%, 0.5%, 1%, 1.5%, 2%, and 2.5% were selected to study the effects of CNCs on the mechanical properties and swelling behavior of the chitosan hydrogel. The crosslinking reaction between chitosan and glutaraldehyde was confirmed by the presence of a –C═N stretching group at 1548 cm−1 in the Fourier transform infrared spectrum of chitosan hydrogel. The crosslinking degree of the chitosan hydrogel was 83.6%. The X-ray diffraction patterns confirmed that adding CNCs induced a combination of amorphous and crystalline regions in the hydrogel matrix. Mechanical tests showed that the maximum compression of the chitosan hydrogel increased from 25.9 ± 1kPa to 50.8 ± 3kPa with increasing CNC content from 0%−2.5%. Field emission scanning electron microscope images revealed that the pore size significantly increased with the formation of widely interconnected porous structure in gas foamed hydrogels. The in vitro degradation rate of hydrogel decreased with the increase of CNC concentration of the hydrogel. Differential scanning calorimetry (DSC) results showed that the thermal stability of the hydrogel increased with the addition of nanocellulose due to the strong interfacial linkage between nanostructured cellulose and chitosan. All the hydrogels showed maximum swelling ratios greater than 300% in distilled water. CNC-chitosan hydrogels exhibited excellent pH sensitivity and producing the maximum swelling ratio under acidic condition (pH 4.01). As a result of its pH-responsiveness, the CNC/chitosan hydrogel has been evaluated as drug delivery vehicle to the stomach. Curcumin, a less water-soluble drug was used in this study, due to the fact that the fast swellable, superporous hydrogel could release a water-insoluble drug to a great extent. FTIR spectrum indicated that there is no interaction between drug and ingredients present in the hydrogels. The drug release data showed good fitting to Ritger-Peppas model. 0.5% CNC-chitosan hydrogel showed the highest increase of drug encapsulation efficiency and drug release after gas foaming at 40 °C, which was from 41% to 68% and from 0.74 mg/L to 1.61 mg/L, respectively. At the later part of this study, curcumin was extracted using turmeric and incorporated into 0.5% CNC-chitosan hydrogel with a nonionic surfactant (Tween 20), using in situ loading method. The drug release of hydrogel increased from 0.21% ± 0.02% to 54.85% ± 0.77%, with the increase of Tween 20 concentration from 0% to 30% (w/v), after 7.5 h. Moreover, the results revealed that the drug maintained its chemical activity after in vitro release. According to the results of this study, CNC reinforced chitosan hydrogel can be suggested to improve the bioavailability of curcumin for the absorption from stomach and upper intestinal tract.